STRATEGI DAKWAH TAKMIR MASJID DALAM MENANGKAL RADIKALISME AGAMA DI BANYUMAS - ARSAM ARSAM (TASÂMUH, 2019)
Religious radicalism becomes a big problem that endangers the nation's generation and the integrity of the Republic of Indonesia. Because this understanding has spread without limits either through direct contact or through social media. One strategic element to resolve the issue is mosque takmir. Because takmir mosque directly touches with the community. The results of this study are strategies drawn up by the mosque takmir in Banyumas based on the situation and condition of the community which includes strengths, weaknesses and also opportunities and threats that exist in the community. The strategy of preaching takmir of the Nur Sulaiman mosque is infiltration, tolerance, cooperation with the Police Sector through counselling. Refusal to the hard flow, fostering youth mosque, a joint declaration of citizens, takmir, and police to reject radicalism. The strategy of preaching takmir of the Baitussalam mosque is infiltration, collaboration with the Kebarongan Police Station, accommodating Islamic groups, youth coaching. The strategy of preaching takmir of the Jami Huda Pejogol Cilongok Banyumas mosque consists of infiltration, strengthening Nahdliyin practices, silaturrohmi between takmir in the Pejogol village, rejection of the hard flow that enters, fostering adolescent mosques. the preaching takmir strategy of the Great Baitussalam Purwokerto mosque consists of infiltration, tolerance, rejection of prohibited understandings, youth coaching, collaboration with the police and regional government. The strategy of preaching takmir of the Nurul Ulum mosque consists of infiltration, assistance and guidance, publication, rejection of banned organizations, selection of informants. The strategy of preaching takmir of the Darunnajah mosque of IAIN Purwokerto includes infiltration, fostering youth of the mosque (students), selection of informants with moderate insight, actual Koran, rejection of bulletins that are close to radicalism.